Observed supersymmetry in baryon and meson spectra with IBFM, the interacting Boson-fermion model - Dey, Jishnu [UNESP]; Dey, Mira (Elsevier, 1990)
Supersymmetry is already observed in (i) nuclear physics where the same empirical formula based on a graded Lie group described even-even and odd-even nuclear spectra and (ii) in Nambu-BCS theory where there is a simple relationship between the energy gap of the basic fermion and the bosonic collective modes. We now suggest similar relationships between the large number of mesonic and baryonic excitations based on the SU(3) substructure in the U(15/30) graded Lie group.